Use of an indicator to evaluate physician adherence to prescription guidelines for the treatment of heart failure - Márcio Galvão Oliveira; Luiz Carlos Passos; Edval Gomes Santos Júnior; Andrea Cristina Barbosa; Djanilson Barbosa Santos (Universidade de São Paulo, 2013)
The aim of this study was to use indicators to evaluate physician adherence to prescription guidelines for heart failure treatment in a university hospital. This was a prospective cohort study conducted in a university hospital. The information collected at the time of patient admission, including therapeutic indication, absolute contra indications and intolerance, was utilised for the formulation of a guideline adherence indicator (GAI). This indicator was calculated as follows: (the number of patients who used the medication/the number of eligible patients) x 100. The percentage of eligible patients was calculated using the following formula: (the number of eligible patients/the total number patients) x 100. The GAI was applied to a population of 53 patients. Inhibitors of angiotensin-converting enzyme/angiotensin receptor blocker (ACE-I/ARB) combination therapy were used in the greatest percentage of eligible patients (92.4%) and demonstrated the largest GAI value (73.5%). The percentages of patients who were eligible for beta-blockers, spironolactone and digitalis treatments were 81.1%, 52.8% and 60.4%, respectively. The GAI values for the use of beta-blockers, spironolactone and digitalis were 60.4%, 57.1% and 56.2%, respectively. For the studied patient population, the GAI was consistent with the proportion of patients who were eligible to receive digitalis and spironolactone.